AB0373 TREATMENT OF SLE WITH THE IMMUNOPROTEASOME INHIBITOR KZR-616: RESULTS FROM THE FIRST 4 COHORTS OF THE MISSION STUDY, AN OPEN-LABEL PHASE 1B DOSE ESCALATION TRIAL. (2nd June 2020) - Furie, R.; Parikh, S.; Maiquez, A.; Khan, A.; Moreno, O.; Soneira, M.; Kirk, C.; Bomba, D.; Harvey, K.; Farmer, M. K.
Abstract : Background: Non-specific proteasome inhibitors, such as bortezomib (BTZ), target the constitutive proteasome and immunoproteasome and are approved treatments for multiple myeloma 1 . BTZ has also been used to treat systemic lupus erythematosus (SLE) and lupus nephritis (LN); however, treatment emergent adverse events (TEAEs), such as gastrointestinal (GI) effects, hematologic abnormalities, asthenia and peripheral neuropathy, limit its use as a long-term treatment option for chronic autoimmune disease 2 . KZR-616 is a first-in-class selective immunoproteasome inhibitor and is highly active in murine SLE 3 . Subcutaneous (SC) administration of KZR-616 (30 and 45 mg weekly [QW]) was demonstrated as safe and well-tolerated, and successfully achieved target levels of immunoproteasome inhibition in healthy volunteers 4, 5 . Objectives: We report the preliminary safety and efficacy of KZR-616 in the first 4 cohorts of the Phase 1b portion of Study KZR-616-002 in patients with active SLE (NCT03393013 ). Methods: SLE patients (per SLICC Classification Criteria) with SLEDAI ≥4 despite stable background immunosuppressant, anti-malarial, and/or corticosteroid (≤20 mg prednisone equivalent) therapy in this open-label multicentric dose-escalation trial received KZR-616 at doses of 45mg (Cohort 1), 60mg (Cohort 2), or 30mg with escalation to 60mg (Cohorts 2a and 2b) SC weekly through Week 13 (W13) with 12 weeks of follow-up. Efficacy measures included SLEDAI, Cutaneous Lupus Erythematous Disease Area and Severity Index, 28 tender and swollen joint counts, Physicians Global Assessment, Patient Global Assessment, and Patient Assessment of Pain, in evaluable patients (those who received ≥1 month of KZR-616). Results: As of 16 January 2020, 33 patients had enrolled and received at least 1 dose of KZR-616. The majority of TEAEs have been mild or moderate with no reported peripheral neuropathy, prolonged GI-related AEs, and no clinically significant laboratory AEs. There were 3 treatment emergent SAEs, one each of thrombotic microangiopathy (Cohort 2), localized herpes zoster (Cohort 2a), and systemic inflammatory response syndrome (Cohort 2a) with the latter 2 patients completing the full 13 weeks of treatment after resolution. When compared to baseline, improvement in all measures of disease activity were seen at W13 and maintained or improved during the follow-up period, and 94% of evaluable patients had improvements on at least 2 measures/assessments of disease activity. A single patient with active class IV/V nephritis was enrolled on prednisone 10 mg, leflunomide 10 mg, and hydroxychloroquine 200mg/day; nephrotic-range proteinuria at baseline (3.85 g/day) decreased to 0.6 g/day 4 weeks after the last dose of KZR-616. Conclusion: Weekly subcutaneous administration of KZR-616 at 45 and 60 mg was safe and well-tolerated. Evidence of disease suppression at W13 in active SLE patients on stable background therapy was observed. In addition, one study participant with active proliferative nephritis was enrolled with significant reduction in proteinuria. The Phase 2 portion of this study in active proliferative LN is open for enrollment. References: [1]Scott K. et al. Cochrane Database Syst Rev 2016;4:CD010816 [2]Alexander T et al. Ann Rheum Dis 2015;74: 1474–8 [3]Muchamuel T. et al. Ann Rheum Dis 2018;77: A685 [4]Lickliter J. et al. Ann Rheum Dis 2018;77: A1413 [5]Furie R et al. Ann Rheum Dis 2019;78: A776 Disclosure of Interests: Richard Furie Grant/research support from: AstraZeneca, Biogen, Consultant of: AstraZeneca, Biogen, SV Parikh Grant/research support from: Aurinia Pharmaceuticals, EMD-Serono, Consultant of: Aurinia, BMS, GSK, Adonis Maiquez: None declared, Amber Khan: None declared, Orlando Moreno: None declared, Miguel Soneira: None declared, Christopher Kirk Shareholder of: Kezar Life Sciences, LLC, Employee of: Kezar Life Sciences, LLC, Darrin Bomba Shareholder of: Kezar Life Sciences, LLC, Employee of: Kezar Life Sciences, LLC, Ken Harvey Shareholder of: Kezar Life Sciences, LLC, Employee of: Kezar Life Sciences, LLC, Mary Katherine Farmer Shareholder of: Kezar Life Sciences, Employee of: Kezar Life Sciences